Karel Appel : Sculpture: a Catalogue Raisonné - Appel, Karel; Kuspit, Donald (New York : Harry N. Abrams Inc. Publishers New York, 1994)
Rebellious, spontaneous, childlike, avant-garde, intensely personal, passionately colorful - all these characterize the completely unique sculptures of the renowned artist Karel Appel. Karel Appel Sculpture is the first complete volume on his sculptures, from his earliest pieces of 1947, when the young founder of the CoBra movement burst on the scene in Europe, to Appel's most recent works of his past year. In the text, Donald Kuspit delves into the intense emotion that he says is the essence of Karel Appel's art. He follows the artist's mental and artistic development ; touching on threads that run throughout his works : the childlike aspects of his art, the role of insanity, the anticipation of death, his fluid, constantly changing creative expression. With one hundred rich colorplates and over 150 black-and-white, Karel Appel Sculpture represents a catalogue raisonné of every work the artist has created. The entire range of Appel's sculptural career to date is here : from his notorious Questioning Children relief assemblages which brought him to the forefront of the avant-garde art scene in Amsterdam in 1948-49 ; to the totem-like structures of the late 1940s ; the organic shapes of his rough, wildly painted olive-tree roots of 1960 ; the Standing Nudes of 1980s ; to his latest works - the Pyre Series - massive, complex sculptural fantasies that combine painting , sculpture, architecture, and found objects and are based on folk legends and primitive myths.
bibliog., coll. p. 183-186
biog. p. 173-177, Exhibition History p. 178-182
Engels
boek
Keywords: Appel, Karel